2020
DOI: 10.1055/s-0040-1715127
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Limitations of Leap Motion from a Developers', Physical Therapists', and Patients' Perspective

Abstract: Background Physical rehabilitation exergames (PREGs) are suitable for motivating patients toward completing treatments. Leap Motion (LM) is a motion sensor that may be useful for developing PREGs targeted at hands and fingers rehabilitation. Therefore, knowing the advantages and limitations of LM is relevant to understand under which conditions this sensor may be suitable. Objective In this article, we present a qualitative study to identify the main advantages and limitations of LM for PREGs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…To date, different studies have analyzed the validity [49], feasibility [50], and usability [32] of LMC for use in neurorehabilitation. Several RCTs have assessed the effect of immersive or non-immersive VR on UE motor function recovery [51][52][53], and consequently, some reviews have been carried out [54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…To date, different studies have analyzed the validity [49], feasibility [50], and usability [32] of LMC for use in neurorehabilitation. Several RCTs have assessed the effect of immersive or non-immersive VR on UE motor function recovery [51][52][53], and consequently, some reviews have been carried out [54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Leap Motion was not favorable with manual measurement (31)(32)(33)(34). Under such circumstances, the threshold value of features could not be directly determined by clinical experience.…”
Section: Discussionmentioning
confidence: 97%
“…In similar studies, a portable infrared camera called Leap Motion has been reported in functional assessments of hand rehabilitation ( 22 ). Researchers also found that the measurement result of Leap Motion was not favorable with manual measurement ( 31 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the research field of automatic hand ROM measurement, the clinical agreement was unfavorable in related studies. 38 , 47 49 The reason might be the lack of large datasets for hand pose estimation compared with face or body, 20 and the occlusion of the hand is still a challenging task for manual annotation. 50 Moreover, hand datasets for medical applications or clinical settings did not exist.…”
Section: Discussionmentioning
confidence: 99%